Distress and pleasure indicators in health care workers on the COVID-19 front line (Revista Latino-Americana de Enfermagem, 2022)
Objective: to evaluate distress and pleasure indicators in healthcare workers on the front line of care for suspected or confirmedCOVID-19 cases. Method: an exploratory, analytical and crosssectionalstudy with a quantitative approach. The studied sampleconsisted of 437 health professionals invited by electronic means,who answered the questionnaire on sociodemographic information,occupational aspects and clinical conditions. Distress and pleasureat work were considered as outcomes, which were analyzed withmultinomial logistic regression regarding the associated independentvariables. Results: Most of the participants were female (71.0%),nurses (55.6%), with a weekly working shift of 40 hours ormore (75.8%); 61.6% of the participants suffered from mentaldistress. The psychosocial characteristics of high-strain work and lowsocial support were reported by 23.8% and 52.9% of the participants,respectively. In the multiple analysis, distress and lack of pleasureat work were associated with high job strain, low support from coworkersand mental distress. The profession is also associated withdistress at work. Conclusion: distress and lack of pleasure at workare associated with occupational characteristics and mental strainamong health care workers in the COVID-19 scenario.